2007
DOI: 10.1194/jlr.m600353-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ABCG5/G8 overexpression reduces apoB-lipoproteins and atherosclerosis when cholesterol absorption is inhibited

Abstract: We previously reported that liver-specific overexpression of ABCG5/G8 in mice is not atheroprotective, suggesting that increased biliary cholesterol secretion must be coupled with decreased intestinal cholesterol absorption to increase net sterol loss from the body and reduce atherosclerosis. To evaluate this hypothesis, we fed low density lipoprotein receptor-knockout (LDLr-KO) control and ABCG5/ G8-transgenic (ABCG5/G8-Tg)3LDLr-KO mice, which overexpress ABCG5/G8 only in liver, a Western diet containing ezet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 68 publications
4
30
0
Order By: Relevance
“…In contrast, liverspecific transgenic mice had reduced lesions only when fed Ezetimibe (a synthetic NPC1L1 inhibitor) suggesting that intestinal sterol absorption compensates for the athero-protective effects of hepatic ABCG5/ABCG8 (49). This hypothesis is supported by the recent finding that loss of NPC1L1 reverts the sitosterolemic phenotype of Abcg5…”
Section: Abcg5 and Abcg8supporting
confidence: 72%
“…In contrast, liverspecific transgenic mice had reduced lesions only when fed Ezetimibe (a synthetic NPC1L1 inhibitor) suggesting that intestinal sterol absorption compensates for the athero-protective effects of hepatic ABCG5/ABCG8 (49). This hypothesis is supported by the recent finding that loss of NPC1L1 reverts the sitosterolemic phenotype of Abcg5…”
Section: Abcg5 and Abcg8supporting
confidence: 72%
“…Absence of ABCG5, ABCG8 or both results in an elevation of plant sterols in the tissues and blood and a failure to excrete sterols into bile [24][25][26][27][28][29][30][31] . Over expression of ABCG5 and ABCG8 in mice transgenic for the human genes led to a super saturation of cholesterol in bile and protected animals against atherosclerosis.…”
Section: Pathophysiology Of Sitosterolemiamentioning
confidence: 99%
“…Ezetimibe may lower plasma levels of ApoB lipoproteins through its reduction of hepatic cholesterol concentrations, leading to decreased atherogenic ApoB lipoprotein production [92]. Additionally, kinetic studies have shown that ezetimibe reduction of cholesterol delivery to the liver increases the hepatic uptake and catabolism of ApoB-100-containing lipoproteins VLDL, IDL and LDL [46], which would further reduce ApoB levels.…”
Section: Apob-100mentioning
confidence: 99%